Cultural and architectural study of the Sanctuary of Santa Rosa de Lima in the tradition «El rosal de Rosa» («The Rosebush of Rosa») and its impact as a world heritage site - Romero Villafuerte, Lucero (2023)
The present article will approach the tradition «The Rosebush of Rosa», which is part of the Peruvian Traditions, a representative work of Ricardo Palma. We will focus on the importance of studying historical monuments, such as the one presented in this tradition, the Sanctuary of Santa Rosa de Lima. This in order that, as this is a cult building, currently considered a World Heritage Site by UNESCO, it generates a new perspective of society with respect to the use that is given to it and the streets that surround it.